2008
DOI: 10.3171/jns/2008/109/11/0849
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem glioma progression in juvenile and adult rats

Abstract: Objective Brainstem gliomas are common in children and have the worst prognosis of any brain tumor in children. On the other hand, brainstem gliomas are rare in adult, and clinical studies have suggested different biological behavior between young and adult. The present study was designed to develop an orthotropic C6 brainstem glioma model in young and adult rats, and to investigate the tumor biological behavior in the two age groups. Methods C6 glioma cells were stereotactically implanted into the pons of y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 40 publications
1
19
1
Order By: Relevance
“…Rats in groups A and C exhibited a ‘decrease-increase-decrease’ pattern of weight gain, which is in contrast with the data reported by Liu et al (19). Subsequent to implantation, the stress response following surgery and anesthesia caused a short-term reduction in eating and drinking, which resulted in weight loss.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Rats in groups A and C exhibited a ‘decrease-increase-decrease’ pattern of weight gain, which is in contrast with the data reported by Liu et al (19). Subsequent to implantation, the stress response following surgery and anesthesia caused a short-term reduction in eating and drinking, which resulted in weight loss.…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, in the present study, hydrocephalus appeared earlier in the juvenile rats, which resulted in shorter survival times. This is consistent with the results from a study by Liu et al (19). …”
Section: Discussionsupporting
confidence: 94%
“…In an animal model of brainstem glioma, the authors found that the tumors were more diffuse in young rats and relatively focal in adult rats. Furthermore, brainstem gliomas in young rats were more proliferative and had less apoptotic cells than those in adult rats [20]. Their findings suggested that the growth pattern and invasiveness differed between the groups.…”
Section: International Journal Of Neurosciencementioning
confidence: 96%
“…These and other data suggest that BSG is a unique glioma subtype with biological and molecular pathology mechanisms different from common gliomas (6). Discerning the key differences between pediatric and adult BSG may prove indispensable to the fight against pediatric BSG (10), a fight that has not yielded many positive victories in recent years (1).…”
Section: Introductionmentioning
confidence: 92%